Six Sigma methodology for reducing defects in manufacturing industry - a case study. (2017) - Singh, Jagdeep; Singh, Harwinder; Singh, Deepinder; Singh, Virender
Owing to global competition in manufacturing sectors, customer demand for high quality product and for product variety is continuously increasing. Consequently, it has become necessary to enhance productivity and performance in order to make the process robust to quality. The present work deals with the application of DMAIC technique in manufacturing industry for quality improvement and reduction of muffler line defects. The DMAIC cycle has been applied to the critical product under study to ascertain the important benefits occurring for business improvement in the manufacturing industry of Northern India. The findings revealed significant enhancement in sigma level from 2.89 to 3.16 and process yield was increased from 91.73% to 95.19%. This study is an attempt to access the performance of Six Sigma approach through systematically implementation of DMAIC cycle. These enhanced sigma levels leads to high quality and fewer variations. The results showed that the rejection rate was reduced from 8.27% to 4.81% and saving in cost of Rs. 940, 800/- has been achieved.